Where will you be after one year and a half as a refugee?: Linguistic borders and bureaucratic mazes - Mateus, S.; Santos, P. (Borders and Borderlands: explorations in identity, exile, translation and transition, 2021)
Four years have passed since asylum applications in Europe reached their peak with a registered number of 1.3 million requests. Since then, there’s been a consistent remission of the influx. While numbers might contribute to a political rhetoric claiming that the so-called European migrant crisis has come to an end, the critical scenarios regarding asylum seekers and refugees are far from being over. After a challenging journey, in host countries, forced migrants must not only overcome linguistic and bureaucratic obstacles, but also deal with the inefficiency of organizations in providing support, which demonstrates how highly bureaucratized systems act as a further frontier that refugees must somehow cross. In the effort to do so, forced migrants have to wait years in a condition of statelessness and disempowerment, in order to have the right to be more than a stranger. Such state of abeyance is socially produced and constitutes a significant dimension within power structures. In this chapter, we shall focus on the obstacles and challenges faced by forced migrants and how welcoming practices and integration policies of hosting countries generate further barriers and borders. Drawing from the results of 14 semi-structured interviews to asylum seekers and refugees hosted in Lisbon, we outline and explore linguistic boundaries and bureaucracy as state-generated borders. This study is part of a greater body of research within the framework of the PandPAS project (Mateus et al., 2019).